Digitalizing the community health information system improved women’s retention on the maternal continuum of care pathway in northwest Ethiopia: A quasi-experimental study - Tesfahun Hailemariam; Asmamaw Atnafu; Lemma Derseh Gezie; Jens Johan Kaasbøll; Jörn Klein; Binyam Tilahun (PLoS ONE, 2025)
Background Retaining women on the maternal continuum of care pathway remains a significant challenge for the healthcare system. Digitalizing primary healthcare system using community health workers is a key strategy to enhance maternal healthcare utilization in Ethiopia. However, the effectiveness of digitalizing community health system using frontline health system workers is uncertain. Objective To determine the effect of electronic community health information system intervention on maternal continuum of care in northwest Ethiopia. Methods A pre-post experimental study was conducted in Wogera district, northwest Ethiopia. Data were collected at household level from April to May 2022 including a total of 830 women with children with age less than one-year. A log-binomial logistic regression model was used to estimate the effect of electronic community health information system on the maternal continuum of care and its predictors. Relative risk with a 95% confidence interval was reported, with a p-value of <0.05 considered statistically significant. Results The study revealed that 10.6% women were fully retained on the maternal continuum of care before the intervention while 32.5% after the intervention(p < 0.001). Women in the intervention cluster had 3.12 times higher coverage of maternal continuum of care(ARR: 3.12,95%CI: 2.20–4.41). In addition, primary education(ARR: 1.54, 95%CI:1.14, 2.08), secondary and above education(ARR: 1.61, 95%CI:1.08,2.39); pregnancy intention (ARR: 1.67, 95%CI: 1.11,2.51), and women’s autonomy in healthcare decision making (ARR: 2.02, 95%CI: 1.03, 3.97) were significantly associated with maternal continuum of care. Conclusions Electronic community health information system improved maternal continuum of care. Maternal health service programs in rural should consider the implementation of electronic community health information system. Provision of women’s education, prevention of unintended pregnancy, and enhancement of autonomy of women in healthcare decision making should be emphasized to improve maternal continuum of care.